2018
DOI: 10.1016/j.semradonc.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Liver Disease and Modern Radiotherapy

Abstract: Modern radiotherapy techniques have enabled high focal doses of radiation to be delivered to patients with primary and secondary malignancies of the liver. The current clinical practice of radiation oncology has benefitted from decades of research that have informed how to achieve excellent local control and survival outcomes with minimal toxicities. Still, one of the most devastating consequences of radiation to the liver remains a challenge: radiation induced liver disease (RILD). Here, we will review the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 110 publications
1
66
2
Order By: Relevance
“…Given that the majority of the patients in our analysis were less than 36 months of age (65%) and assigned to receive RT (94%), it is important to consider the potential risk for SOS in treating patients with biliary RMS. Newer RT techniques such as intensity‐modulated proton therapy may aid in reducing this risk 29 …”
Section: Discussionmentioning
confidence: 99%
“…Given that the majority of the patients in our analysis were less than 36 months of age (65%) and assigned to receive RT (94%), it is important to consider the potential risk for SOS in treating patients with biliary RMS. Newer RT techniques such as intensity‐modulated proton therapy may aid in reducing this risk 29 …”
Section: Discussionmentioning
confidence: 99%
“…Adverse events of anorexia, nausea, exacerbation of liver damage, and bone marrow suppression are often reported after radiotherapy, and most of these events are resolved within a few weeks [ 23 , 24 ]. Li et al reported that no patients treated with radiotherapy experienced any serious adverse events necessitating discontinuation of the radiation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced liver disease (RILD) has gained attention recently because of concerns for the safety of radiotherapy. Compared with classic RILD due to dose-limiting complications, non-classic RILD, which occurs with radiotherapy using CT-based planning, causes increases in transaminase and bilirubin [ 23 , 24 ]. Our patients showed no significant adverse events after radiotherapy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional radiotherapy can prolong survival for patients with resectable liver cancers [1] but it offers limited efficacy for the treatment of unresectable primary and metastatic liver cancers mainly due to the low whole liver tolerance to radiotherapy [2, 3]. Stereotactic body radiation therapy (SBRT), which is an accurate external beam irradiation method to deliver conformal high doses in a few fractions, has been proven to be an effective treatment modality for liver cancers with an elevated rate of local control [38].…”
Section: Introductionmentioning
confidence: 99%